Surgery Associated with Radiotherapy for Treatment of Giant Squamous Cell Carcinoma in Hand - Mendes, Bruna Mizobutsi; MD, Frederico Gustavo Neiva Ellinger; MD, Mariam Patricia Auada Souto; PhD; MD, Luis Ricardo Martinhao Souto; PhD (Archives of Clinical and Medical Case Reports, 2019)
Squamous cell carcinoma is the most common tumor in the hand, with actinic keratosis being its precursor lesion. It is a common tumor in light-skinned individuals with a history of excessive sun exposure and advanced age. It presents a wide variety of clinical forms, which can generate diagnostic doubt. The combination of clinical and pathological evaluations, together with detailed anamnesis, is the best way to achieve at the final diagnosis. The gold standard treatment for these tumors is surgical excision of the lesion with adequate safety margins; in some cases adjuvant radiotherapy is an excellent option. In this paper, we review the subject addressed and report the case of a patient with giant squamous cell carcinoma in one hand, with eight months of evolution, treated by surgical excision and adjuvant radiotherapy; the treatment was successful and preserved the motor function of the patient's hand.